2022
DOI: 10.3390/coatings12111635
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Process Development and Rig Validation of Slurry Environmental Barrier Coatings for SiC Ceramic and SiC Composite Sub-Components

Abstract: The process scale-up of fully oxide-based environmental barrier coatings (EBCs) on sintered SiC and chemical vapor infiltration (CVI) SiC/SiC ceramic matrix composite (CMC) sub-components was investigated using various slurry manufacturing processes (dip, spray, spin–dip). The performance of EBC-coated sub-components (SiC heating element, SiC/SiC ceramic matrix mini-composite, SiC airfoil, SiC/SiC CMC airfoil) was evaluated in steam oxidation and combustion rigs. Steam oxidation was conducted at 1427 °C in 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…38 Slurry-type coating deposition processes may be an option most readily available for complex geometries desired with additively manufactured SiC-base composites. 39…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Slurry-type coating deposition processes may be an option most readily available for complex geometries desired with additively manufactured SiC-base composites. 39…”
Section: Discussionmentioning
confidence: 99%
“…Standard deposition methods for high‐temperature ceramic coatings focus on plasma spray processes that are primarily line‐of‐sight 38 . Slurry‐type coating deposition processes may be an option most readily available for complex geometries desired with additively manufactured SiC‐base composites 39 …”
Section: Discussionmentioning
confidence: 99%
“…The silicon bond coat improves the adhesion between the coating and substrate , but the silicon imposes a temperature limit to an EBC, given its melting temperature of ~1,416 °C (Desai, 1986;Zhang et al, 2022). Therefore, this has started the development of alternative EBC systems with different bond coats (Anton et al, 2020;Harder, 2020;Lee et al, 2022;Zhang et al, 2022). Comprehensive reviews of other EBC systems and compositions can be found in separate publications Paksoy and Xiao, 2023).…”
Section: Purpose Of Tbcs and Ebcsmentioning
confidence: 99%
“…Identifying and quantifying boron concentrations are important as boron increases the rate of oxidation in EBCs (Lee et al, 2021;Lee et al, 2022). Furthermore, the solubility limit of boron at temperature increases, which could also contribute to accelerated oxidation at higher temperatures (Knauf et al, 2020).…”
Section: Bond Coatmentioning
confidence: 99%
“…Silicon carbide (SiC) ceramics have excellent properties, i.e., a high strength, high modulus, low thermal expansion, high thermal conductivity, and good corrosion resistance, enabling their widespread use in the nuclear, semiconductor and aerospace industries [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Densification of SiC ceramics is extremely difficult due to their strong covalent bonds, leading to a low self-diffusion coefficient (~10 −11 cm 2 /s for C and ~10 −13 cm 2 /s for Si) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%